The SASHT: Personal memories, imaginaries and realities (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
It was in 1994, I remember, after some years of involvement and membership in the less-than-a-decade-old South African Society for History Teaching, that I was “nominated” to become the secretary of the SASHT. It was no extraordinary formality. Most probably it could be viewed as a one-way priorto-conference decision-making by the leadership to ensure no diffi culty at the SASHT General Meeting when it would be announced that a volunteer was needed to fi ll the secretary position. All those present – I remember about 50 to 60 then – “gladly” took note of the “volunteer”, thereby implying that the activities of the SASHT at least would be assured of continuity. I do remember, at the 1994 GM, that the author of All that glitters, Emelia Potenza, dryly observed that the stereotype of having only a woman in the position of secretary should be changed. I cannot remember if the leadership responded to this remark, but it made an impression on me as a 34-year-old. I was tasked to take over from Dr Maritz Broodryk from the erstwhile University of Port Elizabeth. With a PhD in Regional History Studies awarded in 1993, I had in some way only departed with my higher education career. I was excited to also help make a diff erence in the newly established democratic South Africa.
Keywords: 1994; South African Society for History Teaching; democratic South Africa